Introduction to metallic glasses and amorphous metals - Stachurski, Z. H. (Zbigniew H.) (Elsevier, 2021)
An Introduction to Metallic Glasses and Amorphous Metals gives a background on the physics of materials, describing relevant experimental techniques. The book presents the necessary background in physics, thermodynamics, and the mechanics of solids, before moving on to cover elasticity, plasticity, fracture and the anelastic behavior of metallic glasses, relating these properties to chemical composition, atomic arrangement, microstructure, and methods of preparation. In addition, it compares the structure-property relationships specific to metallic glasses with polycrystalline metals and alloys and describes the properties and characteristics of metallic glasses. The general features and behavior of metallic glasses are also analyzed and summarized. The book includes full derivations of theory and equations and presents a compendium of experimental methods used in materials science to characterize and study metallic glasses and amorphous solids. The title is a comprehensive resource for any researcher interested in the materials science of metallic glasses and amorphous materials.